Integrated computer projects - Brooks, Lloyd D. 1942- (St. Paul, Minn. EMCParadigm, 2003)
Presents a series of projects for five clients, simulating real-world business activities. The projects require Microsoft Office applications and Internet research skills.
Keywords: Microsoft Office; Business -- Computer programs; Integrated software -- Problems, exercises, etc